2011
DOI: 10.1128/iai.00048-11
|View full text |Cite
|
Sign up to set email alerts
|

Complementation of Rickettsia rickettsii RelA/SpoT Restores a Nonlytic Plaque Phenotype

Abstract: Spotted fever group rickettsiae are known to produce distinct plaque phenotypes. Strains that cause lytic infections in cell culture form clear plaques, while nonlytic strains form opaque plaques in which the cells remain intact. Clear plaques have historically been associated with more-virulent species or strains of spotted fever group rickettsiae. We have selected spontaneous mutant pairs from two independent strains of Rickettsia rickettsii, the virulent R strain and the avirulent Iowa strain. A nonlytic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…During infection, a portion of the phages may enter the lysogenic cycle instead of the lytic cycle, resulting in turbid plaques. Clark et al (6) found that rickettsial phages that cause lytic infections in cell culture form clear plaques, while nonlytic strains form opaque plaques in which the cells remain intact. Plaque size may correlate with virulence: the plaques produced by foot-and-mouth disease viruses are generally larger than the plaques from attenuated strains and those causing milder clinical illness (8).…”
Section: Resultsmentioning
confidence: 99%
“…During infection, a portion of the phages may enter the lysogenic cycle instead of the lytic cycle, resulting in turbid plaques. Clark et al (6) found that rickettsial phages that cause lytic infections in cell culture form clear plaques, while nonlytic strains form opaque plaques in which the cells remain intact. Plaque size may correlate with virulence: the plaques produced by foot-and-mouth disease viruses are generally larger than the plaques from attenuated strains and those causing milder clinical illness (8).…”
Section: Resultsmentioning
confidence: 99%
“…required for their manipulation. The cumulative results of analyzing insertion sites of pMW1650 indicate that transposition is random in the genomes of R. rickettsii (3,9) and R. prowazekii ( Fig. 2; see also Tables S1 and S2 in the supplemental material).…”
mentioning
confidence: 99%
“…The development of mariner-based transposon systems for rickettsiae (10) has offered unprecedented opportunities in the field. Although the obligate intracellular nature of rickettsiae remains a limiting factor in the study of rickettsial pathogenesis, the application of molecular genetics has led to a number of recent advances (3,5,9). The development of transformation systems for rickettsiae was accomplished in R. prowazekii but necessitated extensive cell culture passage and selection for clonal isolation by limiting dilution (10,16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transposon mutagenesis has also been successfully applied to R. rickettsii (6, 7) and Rickettsia monacensis transformed to express GFPuv (green fluorescent protein with maximal fluorescence when excited by UV light) and a chloramphenicol resistance marker (8). Furthermore, targeted gene knockout by homologous recombination has been achieved in R.…”
Section: Introductionmentioning
confidence: 99%